Characters in Audio Visual-Based Teaching Materials in Thematic Learning in Elementary Schools - Beni Azwar; Deri Wanto; Yurika Nopianti (Tadbir : Jurnal Studi Manajemen Pendidikan, 2022)
This scientific article is motivated by the lack of character in students, where as we know today's technological advances can make the character decline in students, but if technology is used properly there will be many benefits, where most students in Indonesia currently With gadgets, technological advances can have both positive and negative impacts. The purpose of this research is to instill the character of students through the use of audio-visual-based teaching materials, such as videos. This study uses a qualitative method with the type of library research (library research), while data collection uses documentation techniques, namely data collection or from books or literatures and journals that discuss "Character in Audio-visual Based Teaching Materials in Thematic Learning. in elementary school". The data analysis technique uses the technique of drawing conclusions by identifying various special characteristics of a message in an objective, systematic and generalist manner. The results of this study are Characters in Audio-visual-Based Teaching Materials In Thematic Learning in Elementary Schools, of course there are various ways that a teacher can do in instilling character in students, one of which is here by using audio-visual-based teaching materials with theme 4 (healthy is healthy). important) sub-theme 3 (how to maintain the health of the circulatory system in humans) in fifth grade elementary school there are 8 characters that teachers can instill, the first being religious, the second being disciplined, the third being environmental care, the fourth being curiosity, the fifth being being responsible, the sixth being independent. , the seventh is social care, the eighth appreciates achievement.